The impact of growth on unemployment in a low vs. a high inflation environment - Mewael F. Tesfaselassie; Maik Wolters (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
During the 1970s, industrial countries, including the US and continental Europa, experienced a combination of slow productivity growth and high unemplyoment. Subsequent research has shown that the standard model of unemployment actually gives counterfactual predictions. Motivated by the observation that the 1970s were also characterized by high and rising inflation, Tesfaselassie and Wolters examine the effect of growth on unemployment in the presence of nominal price rigidity. The authors demonstrate that the effect of growth on unemployment may be positive or negative. Faster growth leads to lower unemployment if the rate of inflation is high enough. There is a threshold level of inflation below which faster growth leads to higher unemployment and above which faster growth leads to lower unemployment. The threshold level in turn depends on labor market characteristics, such as hiring efficiency, the job destruction rate, workers' relative bargaining power and the opportunity cost of work.
urn:nbn:de:hebis:30:3-431590
Keywords: E24; E31; 330; growth; trend inflation; unemployment